A disciplina percepção musical no contexto do bacharelado de Música da UFPB uma investigação à luz de perspectivas e tendências pedagógicas atuais. - Anjos, João Johnson dos (2011)
This study aims at investigating the universal context in which the Subject in Musical Perception is inserted and at the same time to understand what are the prospects which could predominantly disrupt your didactic project, as well as to identify not only problems but also alternatives to handle these. Through collaboration with our colleagues working in this area and also the students who take the course, it was possible to observe relevant aspects related to the structure, pedagogy and conceptual issues. In obtaining this data, we used quantitative research, through interviews with two segments, namely teachers and students of the Bachelor, and that brought transparency and clarification to this data. The results are presented along with the testimonials and some tables easy to understand, accompanied by the research‟s personal considerations and reflections. Initially a bibliographic review was done, in order to understand the context through which covers the discipline, as well as meets the academic studies that deal with the issue, allowing therefore understanding the problems, complaints and proposals submitted by other authors. Sorting the statements, brought educational and enlightening contributions to the discipline.